1984
DOI: 10.1007/bf00279307
|View full text |Cite
|
Sign up to set email alerts
|

Distal duplication 14q: Report of three cases and further delineation of the syndrome

Abstract: Three cases of distal duplication 14q are presented. The first two cases are cousins in a kindred segregating a balanced translocation t(14;18)(q31;q23). The third case resulted from a maternal translocation t(14;18)(q24;p11). By review of these cases and those previously reported, a distal duplication 14q syndrome is further delineated. Common features include postnatal growth retardation, mental retardation, hypotonia, microcephaly, slanted palpebral fissures, ocular hypertelorism, sparse eyelashes and eyebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Since the parental karyotypes were normal, the inv dup(14q) associated with a terminal 14q deletion in this report might have been caused by the simplest model involving a U-type exchange that caused an end-to-end fusion and that led to a dicentric chromosome; during anaphase, the dicentric chromosome could break and result in a chromosome with an inverted duplication and loss of chromosomal material distal to the site of recombination [Weleber et al, 1976;Mitchell et al, 1994; Weinstein et al [1977]; Sklower et al [1984]; Carr et al [1987]; Wakita et al [1988]; Masada et al [1989]; Schinzel [2001]; Sonoda et al [2001]. Kondoh et al, 2003;van Buggenhout et al, 2004].…”
Section: Discussionmentioning
confidence: 95%
“…Since the parental karyotypes were normal, the inv dup(14q) associated with a terminal 14q deletion in this report might have been caused by the simplest model involving a U-type exchange that caused an end-to-end fusion and that led to a dicentric chromosome; during anaphase, the dicentric chromosome could break and result in a chromosome with an inverted duplication and loss of chromosomal material distal to the site of recombination [Weleber et al, 1976;Mitchell et al, 1994; Weinstein et al [1977]; Sklower et al [1984]; Carr et al [1987]; Wakita et al [1988]; Masada et al [1989]; Schinzel [2001]; Sonoda et al [2001]. Kondoh et al, 2003;van Buggenhout et al, 2004].…”
Section: Discussionmentioning
confidence: 95%
“…While a number of patients with 14q duplications have been reported, most have been due to an inherited balanced translocation, and it is therefore hard to differentiate which anomalies are due to the partial trisomy 14 and which are caused by lack of parts of the other chromosome [Pena et al, 1976;Atkin and Patil, 1983;Sklower et al, 1984;Park et al, 1991]. Only a few cases have been reported that are ''pure'' partial trisomy 14 in which the duplicated segment is similar to our case [Trunca and Opitz, 1977;Pfeiffer and Kessel, 1978;Geormaneanu et al, 1981;Nikolis et al, 1983;Orye et al, 1983;Kaiser et al, 1984;Gilgenkrantz et al, 1990].…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed ten cases resulting from parental translocation [Atkin and Patil, 1983;Cohen et al, 1983;Fryns et al, 1977;Geormaneanu et al, 1981;Markkanen et al, 1984, Romain et al, 1983, Sklower et al, 1984Turleau et al, 19841, one case of de novo unbalanced translocation [Bridgman and Butler, 19801, one case resulting from a maternal pericentric inversion [Trunca and Opitz, 19771, and two cases of tandem duplication of distal 14q [Nikolis et al, 1983;Orye et al, 19831. Case reports and comparison studies of several investigators [Atkin and Patil, 1983;Markkanen et al, 1984;Sklower et al, 19841 identify most of the clinical findings associated with duplication distal 14q as summarized in Table 11; comparison cases included in Table I1 involved duplicated segments most closely resembling the duplicated segment in patient 2.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of only six published cases involving de novo distal 14q deletions without ring formation [Hreidarsson and Stamberg, 1983;Kawamura et al, 1985;Nielson et al, 1978;Turleau et al, 1984, Yamamoto et al, 19861. Duplications of distal 14q are also rare, although not so infrequent as deletions involving similar segments. Whether a "distal trisomy 14q syndrome" clearly exists has been debated [Atkin and Patil, 1983;Cohen et al, 1983;Fryns et al, 1977;Markkanen et al, 1984;Nikolis et al, 1983;Sklower et al, 1984;Trunca and Opitz, 19771. We present a boy with a terminal deletion ofdistal 14q at a previously unreported breakpoint and describe his phenotype, clinical course, and the findings a t autopsy. A subsequent sister with a duplication ofthe same distal 14q segment is also described.…”
Section: Introductionmentioning
confidence: 97%